What was the notion of ‘the other’ in antiquity? an examination from the perspective of ancient Greeks (2016)
The idea of 'the other' and 'otherness' often relates to the state of a group being different from certain individuals, groups or peoples. Over and over again, a greater or superior group, using certain social distinctiveness, stereotypes, or identities that are often seen as natural and innate, conceives of the lesser group as constituting 'the other(s)', that need(s) refinement, enlightening, or acculturation. In many quarters, 'the other' is conceived as those who do not speak one's language. Going back to the remote Classical antiquity, where one might least expect a prevalence valence of social distinctiveness, identities or stereotypes conjured among definite groups, this paper examines the notion of 'the other' and 'otherness' as it relates to the ancient Greeks and their conception of other peoples. It identifies the term barbarian as the Greeks' equivalent of 'the other'. Etymologically, the barbarian refers to a foreigner, one whose language and customs differ from the native speaker's; and within the Judaeo-Christian civilization, he is a gentile outside the circle of the Christian faith. Using the works of Greek historians such as Herodotus, Strabo, Diodorus and others to provide insight into the Greeks' general perception of these 'others', the paper submits that the word barbarians was used for all non-Greek-speaking peoples, including Egyptians, Ethiopians, Phoenicians, Assyrians, and Persians. The Greeks' thought set the tone for the everyday pejorative meaning given to the barbarian (barbaric, barbarism) as a rude, crude, wild, uncultured, uncivilized person, who has no sympathy with literary culture; he is just a little distinguished from savage or beast.